(798) Input - Output - Tables جداول المدخلات و المخرجات - Horn, Karl-Heinz (INP, 2024)
Emplacement balances or input-output tables are instruments to safe guard a planned and proportional development of the economy. Furthermore they are important and necessary prerequisite of optimation. Their application is possible and necessary not only in the scope of the entire economy but also in partial systems, such as general organisations, enterprises, etc. They can be used to plan and to follow-up production as well as the expenditures of material, labour, and and all other kinds of costs. The main idea of input-output tables is to crasp the interlacements, the links, between branches, or between the production stages of a certain branch or enterprise. This concerns firstly the supply and demand of raw material or semi-finished products, in order to avoid dis- proportions, unused capacities, overproduction, and other kinds of losses.